STRATEGI PEMASARAN DITINJAU DARI 4C DIAMOND FRAMEWORK PADA PT BPR MITRA BUDIKUSUMA MANDIRI KUDUS - Siti Aisyah; Sutono Sutono; Dwi Soegiarto (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to formulate the marketing strategy of PT BPR Mitra Budi Kusuma Mandiri Kudus based on an analysis of the company’s internal and external environment. The research employs a qualitative approach with Strategic Management as the grand theory, specifically focusing on the strategic planning perspective and the strategy formulation stage. Environmental scanning is conducted using the 4C Diamond Framework, which includes Change, Customer, Competitor, and Company, and is subsequently classified into a SWOT analysis and formulated through the TOWS Matrix. The results of the weighting and rating of strategic factors show an IFAS score of 2.80 and an EFAS score of 2.65. Based on the Internal-External (IE) Matrix, the company is positioned in Cell V (Hold and Maintain). This position indicates that the company possesses relatively strong internal capabilities and favorable external opportunities. Therefore, the appropriate strategy is to maintain stability through market penetration and selective product development.  Overall, the formulated marketing strategy is adaptive and relational, emphasizing a balance between growth and prudential principles. This study confirms that a strategic planning approach based on environmental analysis is capable of generating systematic and contextual marketing strategy formulation for microfinance institutions.